Case report: Severe ulcerative dermatitis leading to sepsis in a cat with sporotrichosis by Sporothrix brasiliensis - Cartes, Agustín; Thomson, Pamela; González, Carlos; dos Santos, Amanda Ribeiro; Díaz, Rodrigo; Puyol, Javiera; López, Javiera (Frontiers in Veterinary Science, 2025)
Sporotrichosis caused by Sporothrix brasiliensis is an emerging zoonotic mycosis of great clinical relevance in South America. This case highlights its severe systemic presentation, reported for the first time in a feline patient from Chile. A 1-year-old neutered male cat presented with severe ulcerative dermatitis, developing a dysoxic phenotype of sepsis. Diagnosis was made by cytology, histopathology, fungal culture, and polymerase chain reaction, confirming S. brasiliensis as the pathogen. Treatment included itraconazole associated with potassium iodide. Despite aggressive antifungal therapy and intensive care, based on fluid resuscitation, optimization of analgesia, and administration of vasoactive drugs, the cat developed refractory hypotension and persistent hyperlactatemia, which ultimately led to euthanasia. This report highlights the high pathogenic potential of S. brasiliensis to cause severe systemic disease, even in hosts negative to retroviral infections, and emphasizes the importance of promoting responsible animal management practices to prevent the spread of this infectious agent.